Tracing the origin of the early wet‐season Anopheles coluzzii in the Sahel. (26th May 2017) - Lehmann, Tovi; Weetman, David; Huestis, Diana L.; Yaro, Alpha S.; Kassogue, Yaya; Diallo, Moussa; Donnelly, Martin J.; Dao, Adama
Abstract: In arid environments, the source of the malaria mosquito populations that re‐establish soon after first rains remains a puzzle and alternative explanations have been proposed. Using genetic data, we evaluated whether the early rainy season (RS) population of Anopheles coluzzii is descended from the preceding late RS generation at the same locality, consistent with dry season (DS) dormancy (aestivation), or from migrants from distant locations. Distinct predictions derived from these two hypotheses were assessed, based on variation in 738 SNPs in eleven A. coluzzii samples, including seven samples spanning 2 years in a Sahelian village. As predicted by the "local origin under aestivation hypothesis, " temporal samples from the late RS and those collected after the first rain of the following RS were clustered together, while larger genetic distances were found among samples spanning the RS. Likewise, multilocus genotype composition of samples from the end of the RS was similar across samples until the following RS, unlike samples that spanned the RS. Consistent with reproductive arrest during the DS, no genetic drift was detected between samples taken over that period, despite encompassing extreme population minima, whereas it was detected between samples spanning the RS. Accordingly, the variance in allele frequency increased with time over the RS, but not over the DS. However, not all the results agreed with aestivation. Large genetic distances separated samples taken a year apart, and during the first year, within‐sample genetic diversity declined and increased back during the late RS, suggesting a bottleneck followed by migration. The decline of genetic diversity followed by a mass distribution of insecticide‐treated nets was accompanied by a reduced mosquito density and a rise in the mutation conferring resistance to pyrethroids, indicating a bottleneck due to insecticidal selection. Overall, our results support aestivation in A. coluzzii during the DS that is accompanied by long‐distance migration in the late RS.